The relationship between organizational climate and job satisfaction of kindergarten teachers: a chain mediation model of occupational stress and emotional labor - Xia, Wei; Fan, Yuchen; Bai, Jingyu; Zhang, Qingyi; Wen, Yue (Frontiers in Psychology, 2024)
Organizational climate has been shown to be an important factor associated with teachers' job satisfaction. However, the internal mechanism between them is unclear. The purpose of this study was to investigate whether the relationship between kindergarten organizational climate and kindergarten teachers' job satisfaction was affected by occupational stress and emotional labor. This study employed a questionnaire survey method to gather data from 1091 kindergarten teachers nationwide. It conducted an analysis of the current status of kindergarten organizational climate and the job satisfaction of kindergarten teachers, elucidating the relationship between the two and the underlying mechanisms. Additionally, a chain mediation model was constructed. The findings indicated that: (1) organizational climate, kindergarten teachers' occupational stress and emotional labor all significantly predict kindergarten teachers' job satisfaction directly (2) organizational climate could indirectly influence kindergarten teachers' job satisfaction through three pathways: the separate mediating effect of occupational stress and emotional labor, and the chain mediating effect on both. The research findings highlight the significance of kindergarten organizational climate, occupational stress, and emotional labor in augmenting the job satisfaction of kindergarten teachers, offering valuable insights for the improvement of kindergarten teacher job satisfaction.